2006
DOI: 10.4049/jimmunol.177.5.3421
|View full text |Cite
|
Sign up to set email alerts
|

Stat5 Expression Is Required for IgE-Mediated Mast Cell Function

Abstract: The mast cell (MC) inflammatory response is now linked not only to atopy, but also to arthritis, multiple sclerosis, heart disease, and resistance to bacterial infection. In the current study, we demonstrate that the signal transducer and activator of transcription 5 (Stat5) is rapidly activated by IgE cross-linkage, and that its expression is critical to the MC response. Stat5-deficient (Stat5KO) MC demonstrated a significant decrease in IgE-mediated degranulation, leukotriene B4 production, cytokine secretio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
62
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 30 publications
1
62
1
Order By: Relevance
“…Although these findings contrast to studies performed in murine models (16,17), our results parallels the data by Hundley et al (18) who observed that Kit ligand but not antigen stimulated the phosphorylation of STAT5 in human mast cells.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Although these findings contrast to studies performed in murine models (16,17), our results parallels the data by Hundley et al (18) who observed that Kit ligand but not antigen stimulated the phosphorylation of STAT5 in human mast cells.…”
Section: Discussioncontrasting
confidence: 54%
“…An important activator of STAT5 in these cells is interleukin (IL)-3, which plays a fundamental role in mast cell and basophil biology (14,15). Murine models have revealed that activation of STAT5 is also essential for IgE-mediated mast cell activation that includes degranulation and cytokine production (16,17). Alternatively, IL-10 was shown to inhibit IgE induced STAT5 phosphorylation (17).…”
mentioning
confidence: 99%
“…48 STAT5 is critical for normal mast cell development and survival, and also for IgE-mediated mast cell function. 17,49 More recently, we and others have shown that neoplastic mast cells display constitutive expression of phosphorylated STAT5. 18,19 Moreover, we have previously shown that growth of neoplastic mast cells is inhibited by expression of a dominant negative-acting STAT5 mutant.…”
Section: Discussionmentioning
confidence: 94%
“…The essential role for Stat5, Gab2, and PI3K expression in MC development and function came from knockout mouse analysis. [20][21][22][23][24]53,54 Interestingly, mice deficient in p85 or Gab2 have a profound defect in gastrointestinal MCs, while development of MCs in other tissues remained unaffected. 20 These data are consistent with our observations that cS5 F -induced PI3K activation (via formation of a Stat5/Gab2/p85 signaling complex) promotes in particular the development of gastrointestinal MCs.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] Moreover, recent data have shown that Stat5 and Gab2 are also required for signaling via the high affinity IgE receptor Fc⑀RI that plays a critical role in MC function and allergic response. 23,24 Besides their physiologic role in MCs, accumulating evidence suggests that persistent Stat5 and PI3K activation is frequently found in hematopoietic neoplasms and solid tumors. 25,26 It has also been described that disease-related oncogenic tyrosine kinases like Tel-Jak2, Bcr-Abl, Tel-PDGFR␤, mutated Kit or Flt3 receptors, and the Jak2 (V617F) mutant, detectable in most myeloproliferative disorders (MPDs), induce constitutive activation of Stat5, PI3K and its downstream effector, the serine threonine kinase Akt.…”
mentioning
confidence: 99%